Peningkatan Kemampuan Guru Dalam Menyusun Kelengkapan Mengajar Melalui In-House Training Di SMPN 4 Pasaman - Dasman S.Pd (STKIP Pesisir Selatan, 2016)
AbstrakBased on the observations that have been researchers did To the Teacher in SMP N 4 Pasaman, it was found that the ability of Master in Teaching Completeness Preparing still low. The purpose of this research is to improve the ability of Teacher In Teaching Through Completeness Develop In-House Training at SMP N 4 Pasaman .Penelitian a school action research. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subjects consisted of 9 people Master SMP Negeri 4 Pasaman. Data were collected by using observation sheet. Data were analyzed using persentase.Hasil research shows that through In-House Training can improve Capability Teachers Teaching In Developing Completeness. This is evidenced by the increased ability Completeness Develop Teaching Teachers In the first cycle to the second cycle. On average ability skills of teachers in the Teacher In Capabilities Establish Teaching Completed in the first cycle was 49.33 with less category and the second cycle is 83.66 with both categories.Keywords: Improving the ability of teachers, teaching completeness Develop, In- HouseTraining.